2013
DOI: 10.5120/9939-3997
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Paper Currency Recognition using Fourier Mellin Transform, Hidden Markov Model and Support Vector Machine

Abstract: A paper currency recognition system has a wide range of applications such as self receiver machines for automated teller machines and automatic good-selling machines. In this paper a new paper currency recognition system based on Fourier-Mellin transform, Markovian characteristics and Support Vector Machine (SVM) is presented. In the first, a pre-processing algorithm by Fourier-Mellin transform is performed. The key feature of Fourier-Mellin transform is that it is invariant in rotation, translation and scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Authors of [39] have proposed a system that also identified the Euro currency through the application of image processing steps such as preprocessing and segmentation. After applying the image processing steps, the received value is called a feature vector.…”
Section: Relative Workmentioning
confidence: 99%
“…Authors of [39] have proposed a system that also identified the Euro currency through the application of image processing steps such as preprocessing and segmentation. After applying the image processing steps, the received value is called a feature vector.…”
Section: Relative Workmentioning
confidence: 99%
“…Furthermore, many researchers have studied the Saudi Arabian currency. Unfortunately, they did not provide information about the currency issue and/or the studied denominations as presented in the following studies: [17][18][19][20][21][22].…”
Section: Related Workmentioning
confidence: 99%
“…If a banknote has been in circulation for a long time, it may be difficult to extract accurate banknote recognition features due to its surface being soiled by dirt and sebum from users’ hands. To address this, noise removal is performed as a general preprocessing step using techniques based on the Wiener filter [ 10 , 49 , 55 , 65 , 71 ] or median filter [ 42 , 64 ]. Noise occurring in the imaging process or banknote aging can also be diminished by reducing the gray level of the image beyond the 0–255 range [ 54 , 65 , 71 , 72 ].…”
Section: Banknote Recognitionmentioning
confidence: 99%
“…To address this, noise removal is performed as a general preprocessing step using techniques based on the Wiener filter [ 10 , 49 , 55 , 65 , 71 ] or median filter [ 42 , 64 ]. Noise occurring in the imaging process or banknote aging can also be diminished by reducing the gray level of the image beyond the 0–255 range [ 54 , 65 , 71 , 72 ]. Some studies have presented methods to normalize the brightness and improve the contrast of the image by means of histogram equalization [ 42 , 45 ].…”
Section: Banknote Recognitionmentioning
confidence: 99%
See 1 more Smart Citation